Investigation of the mechanical properties of standard Malaysian rubber with constant viscosity and epoxidised natural rubber using nano-indentation test - Salim, Mohd Azli; Md. Saad, Adzni; Sudin, Mohd Nizam; Rosszainily, Intan Raihan Asni; Donik, Crtomir; Mohd Yusof, Norbazlan (Science and Technology Research Institute for Defence, 2020)
The usage of natural rubber (NR) in the development of laminated rubber-metal spring (LR-MS) for automotive applications has led to the investigation on its mechanical properties. This paper describes the use of nano-indentation test to investigate the mechanical properties of standard Malaysian rubber (SMR) with constant viscosity and epoxidised natural rubber (ENR). The mechanical properties of SMR Constant Viscosity 60 (SMR CV-60) and 25 mole % ENR (ENR 25) reinforced with 0, 20, 40 and 60 phr of carbon black (CB) was investigated. The nano-indentation test was carried out using Berkovich tips at constant load of 2 mN with holding times of 0, 5, 10, 15, and 20 s. It was found that the SMR CV-60 and ENR 25 compounds with 60 phr CB loading recorded the highest hardness and elastic modulus values, and also had the lowest penetration depth. The test also revealed that the hardness and penetration depth were independent to the holding times. In contrast, the indentation elastic modulus was found to be highly affected by the holding time.